The acquisition of expertise in Judo: general and daily activities - Mikel Cepeda Lemus; Carlos Montero Carretero; Luis García González; Benito León del Barco; Damián Iglesias Gallego (Federación Extremeña de Balonmano; University of Extremadura, 2012)
The objective of this research is to analyze the preception that have the judokas of different levels of expertise regarding the general and daily activities. The study sample consisted of regional level judo (n = 9), national (n = 27) and international (n = 40). For data collection questionnaire was used as a measuring instrument, through which the subjects rated each activity from four dimensions: concentration, physical exertion, fun and performance. The international judokas stressed the diet as the most important activity to improve performance within the overall activities. With regard to daily activities sleep all judokas highlighted as the most important activity to improve performance.    Key words: Deliberate practice, performance, expertise, judo.